Radical Surgery in Patients With Residual Disease After (Chemo)Radiation for Cervical Cancer. Issue 7 (1st September 2014) - Boers, Aniek; Arts, Henriette J.G.; Klip, Harry; Nijhuis, Esther R.; Pras, Elisabeth; Hollema, Harry; Wisman, G. Bea A.; Nijman, Hans W.; Mourits, Marian J.E.; Reyners, Anna K.L.; de Bock, Geertruida H.; Thomas, Gillian; et al.
Abstract : Objective: The aim of this study was to determine possible impact of routinely scheduled biopsies and more radical surgery for residual central disease in locally advanced cervical cancer after (chemo)radiation. Methods/Materials: Data were analyzed of a consecutive series of cervical cancer patients (The International Federation of Gynecology and Obstetrics stages IB1-IVA) treated with (chemo) radiation between 1994 and 2011. Patients underwent gynecologic examination with biopsies 8 to 10 weeks after treatment. Since 2001, larger biopsies by electric loop excision were taken, and more radical surgery (type III hysterectomy or exenteration) was performed for central residual disease. Primary outcome was locoregional recurrence. Secondary outcomes were treatment-associated morbidity and disease-specific survival. Results: Primary (chemo)radiation was given to 491 cervical cancer patients; 345 patients had a posttreatment biopsy. Viable tumor cells were identified in 84 patients, and 61 patients were eligible for salvage surgery. Residual disease after (chemo)radiation was an independent poor prognostic factor (hazard ratio, 3.59; 95% confidence interval, 2.18–5.93; P < 0.001). After 2001, larger biopsies were more frequently taken (29% vs 76%, P < 0.001), and in patients without viable tumor cells, locoregional recurrence after 2001 decreased from 21% to 10% ( P = 0.01). After 2001, more patients underwent more radical surgery (46% vs 90%) ( P < 0.001). Locoregional recurrence after surgery before 2001 occurred in 6 (46%) of the 13 patients, comparable with 19 (40%) of the 48 ( P = 0.67) after 2001. More radical surgery was not associated with improved disease-specific survival (HR, 0.84; 95% CI, 0.20–3.46; P = 0.81) but did result in significantly more severe morbidity. Conclusion: More radical surgery in patients with (minimal) central residual disease identified by routine biopsy 8 to 10 weeks after (chemo)radiation does not improve survival and should not be recommended.